Sustainable Development Goal Aligned Business Practices - Sonali Bhattacharya; Dipasha Sharma (Australasian Accounting, Business and Finance Journal, 2023)
In this collection of fifteen articles we revisited the various aspects of sustainable development goals and how industries are proactively strategizing to create a greener and healthier world.
Keywords: Editorial; Volume 17 Issue 1; Special Issue; Sustainable Development Goals; Aligned Business Practices; India; SDGs